2017
DOI: 10.29252/jgbfnm.14.1.22
|View full text |Cite
|
Sign up to set email alerts
|

The Nurses' Quality of Life Based on Burnout, Perceived Social Support and Psychological Hardiness

Abstract: Background: Nurses are responsible for maintaining and improving the health and quality of life of patients. Therefore, it is important to assess the quality of life of nurses in order to improve it. Quality of life is affected by many variables and among them burnout, perceived social support and psychological hardiness are the leading ones. This study aimed at predicting the quality of life of nurses based on job burnout, perceived social support and psychological hardiness. Methods: This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Our research showed this in the relationships established with the various emotional intelligence factors analyzed. The results for perceived social support suggest that it might be related negatively to burnout scores (Aranda et al, 2004), with a certain degree of involvement in stress control, and adopting adequate coping behaviors (Arrogante et al, 2016;Hatamipour et al, 2017;Scheurer et al, 2012;Stevens et al, 2013). As in the study by Kim (2009), direct involvement of the role of self-efficacy in developing burnout was not corroborated by our data, even though it had a relationship with social support (Simón et al, 2017) and emotional intelligence (Gharetepeh et al, 2015;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research showed this in the relationships established with the various emotional intelligence factors analyzed. The results for perceived social support suggest that it might be related negatively to burnout scores (Aranda et al, 2004), with a certain degree of involvement in stress control, and adopting adequate coping behaviors (Arrogante et al, 2016;Hatamipour et al, 2017;Scheurer et al, 2012;Stevens et al, 2013). As in the study by Kim (2009), direct involvement of the role of self-efficacy in developing burnout was not corroborated by our data, even though it had a relationship with social support (Simón et al, 2017) and emotional intelligence (Gharetepeh et al, 2015;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inapropriate or unexistant social support can lead to an ailment, particularly burnout (Aranda, Pando, & Pérez, 2004). Similarly, social support constitutes one of the most relevant personal resources in determining the wellbeing and quality of life of nursing personnel (Arrogante, Pérez-García, & Aparicio-Zaldívar, 2016;Hatamipour, Hoveida, Rahimaghaee, Babaeiamiri, & Ashoori, 2017).…”
Section: The Role Of Emotional Intelligence Perceived Social Supportmentioning
confidence: 99%
“…However, social support had a significant impact on improving quality of life ( Vafaei et al, 2020 ). Nurses’ quality of life and job performance are influenced by their hardiness ( Hatamipour et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' QOL is an important topic of study because it is related to many professional issues and variables, such as job satisfaction (Andresen et al, 2017;Makabe et al, 2018), work environment (Dos Santos et al, 2018), ITL (Andresen et al, 2017) and burnout (Garbóczy et al, 2021;Hatamipour et al, 2017;Khatatbeh, Khasawneh, et al, 2021).…”
mentioning
confidence: 99%